ECG diagnosis of native heart ventricular tachycardia in a heterotopic heart transplant recipient. Issue 3 (1st March 1999) - Vanderheyden, M; de Sutter, J; Goethals, M
Abstract : A case is reported of haemodynamic collapse in a 51 year old male heterotopic heart transplant recipient caused by native heart ventricular tachycardia. An accurate diagnosis was made by selective right and left sided electrocardiography. Synchronised electrical cardioversion of the native heart (200 J) resulted in restoration of sinus rhythm with prompt relief of symptoms and amelioration of the clinical situation.